Utility of Cardiovascular Magnetic Resonance-Derived Wave Intensity Analysis As a Marker of Ventricular Function in Children with Heart Failure and Normal Ejection Fraction - Ntsinjana, Hopewell N.; Chung, Robin; Ciliberti, Paolo; Muthurangu, Vivek; Schievano, Silvia; Marek, Jan; Parker, Kim H.; Taylor, Andrew M.; Biglino, Giovanni (Frontiers in Pediatrics, 2017)
ABSTRACT Objective: This study sought to explore the diagnostic insight of CMR-derived wave intensity analysis to better study systolic dysfunction in young patients with chronic diastolic dysfunction and preserved ejection fraction, comparing it against other echocardiographic and CMR parameters. Background: Evaluating systolic and diastolic dysfunction in children is challenging, and a gold standard method is currently lacking. Methods: Patients with presumed diastolic dysfunction (n=18; 9 aortic stenosis, 5 hypertrophic and 4 restrictive cardiomyopathy) were compared with age-matched control subjects (n=18). All patients had no mitral or aortic incompetence, significant aortic stenosis or reduced systolic ejection fraction (EF). E/A ratio, E/E’ ratio, deceleration time and isovolumic contraction time (IVCT) were assessed on echocardiography, and indexed left atrial volume (LAVi), acceleration time (AT), ejection time (ET) and wave intensity analysis were calculated from CMR. The latter was performed on CMR phase-contrast flow sequences, defining a ratio of the peaks of the early systolic forward compression wave and the end-systolic forward expansion wave (FCW/FEW). Results: Significant differences between patients and controls were seen in the E/E’ ratio (8.7±4.0 vs. 5.1±1.3, p=0.001) and FCW/FEW ratio (2.5±1.6 vs. 7.2±4.2 x10-5m/s, p<0.001), as well as –as expected– LAVi (80.7±22.5 vs. 51.0±10.9 mL/m2, p<0.001). In particular, patients exhibited a lower FCW (2.5±1.6 vs. 7.2±4.2 x10-5m/s, p<0.001) in the face of preserved EF (67±11% vs. 69±5%, p=0.392), as well as longer IVCT (49±7 vs. 34±7 ms, p < 0.001) and ET/AT (0.35±0.04 vs. 0.27±0.04, p < 0.001). Conclusion: This study shows that the wave intensity derived ratio summarizing systolic and diastolic function could provide insight into ventricular function in children, on top of CMR and echocardiography, and it was here able to identify an element of ventricular dysfunction with preserved EF in a small group of young patients.